Application of the Al Miftah Lil Ulum Method to Improve Students' Ability to Read the Yellow Book at Darul Karomah Mandaran Pasuruan Islamic Boarding School Junior High School - Abdul Khamid; Abdulloh Safiq; Miftakhul Munir (Indonesian Journal of Islamic Religion and Culture, 2024)
One potential solution to enhance students' proficiency in reading the Yellow Book is to implement the Al-Miftah Lil Ulum method. The objective of this study is to determine the impact of applying the Al-Miftah Lil Ulum approach at Darul Karomah Mandaran Pasuruan Middle School on students' proficiency in reading the Yellow Book. This research employs an experimental methodology with a quasi-experimental research design. Data collection techniques include observation, documentation, and tests. The research sample consists of students from Darul Karomah Middle School. The findings indicate an improvement in students' ability to read the Yellow Book, as demonstrated by hypothesis testing using the T-test, with a significance value (0.000) less than 0.05. Furthermore, the application of the Al-Miftah Lil Ulum method has been observed to have a significant effect, as documented by the researcher. It is hoped that this research will contribute to a deeper understanding of the Al-Miftah Lil Ulum method and provide greater insight into its effectiveness